1991
DOI: 10.1063/1.349313
|View full text |Cite
|
Sign up to set email alerts
|

Film growth studies with intrinsic stress measurement: Polycrystalline and epitaxial Ag, Cu, and Au films on mica(001)

Abstract: Growth and microstructure of thin Ag, Cu, and Au films ultrahigh vacuum deposited onto single-crystalline mica(001) have been studied in situ by intrinsic stress measurements (ISM) and low-energy electron diffraction. Depending on the respective substrate temperature, three different modes of Vollmer–Weber (VW) growth can be clearly distinguished by ISM: (i) VW-type nucleation and subsequent columnar grain growth at low temperatures (110 K) where grain-boundary relaxation is the prevailing stress contribution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Extensive in situ thin film stress state studies [7][8][9][10][11][12][13][14] have been performed during the deposition of various single elemental films. It has been revealed that high adatom mobility films like Cu 10,12 and Ag 7-10 usually undergo compressiveto-tensile-to-compressive stress evolution corresponding to the nucleation of islands, coalescence of islands, and postgrowth stages.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive in situ thin film stress state studies [7][8][9][10][11][12][13][14] have been performed during the deposition of various single elemental films. It has been revealed that high adatom mobility films like Cu 10,12 and Ag 7-10 usually undergo compressiveto-tensile-to-compressive stress evolution corresponding to the nucleation of islands, coalescence of islands, and postgrowth stages.…”
Section: Introductionmentioning
confidence: 99%
“…After the tensile stress is decreased to its minimum and the c-axis lattice constant of FST is close to its bulk value, the tensile stress can increase again with further increasing the buffer thickness. This behavior can be attributed to complex dependence of strain on the film thickness by taking the Volmer-Weber growth mode and strain relaxation mechanism into account [24][25][26][27][28][29][30]. For a metal or metallic compound, a typical behavior is that the magnitude of strain can change non-monotoically with film thickness, usually a large tensile strain appears.…”
Section: Resultsmentioning
confidence: 99%
“…As changes of stress are directly related to the relief of misfit-strain, quantitative information on the reduction of the elastic energy by 3D islanding is obtained. Its temperature dependence points to the presence of ESBs (Ehrlich-Schwoebel barriers) [16], which are enhanced by the strain field, thus supporting a kinetic pathway for nucleation and growth of the 3D islands.The experiments were performed in a UHV chamber (base pressure , 1 3 10 210 mbar) equipped with a cantilever beam device for measuring the intrinsic film stress continuously during film deposition and a four-grid LEED optics for in situ control of the epitaxial film quality [17]. …”
mentioning
confidence: 99%
“…The experiments were performed in a UHV chamber (base pressure , 1 3 10 210 mbar) equipped with a cantilever beam device for measuring the intrinsic film stress continuously during film deposition and a four-grid LEED optics for in situ control of the epitaxial film quality [17].…”
mentioning
confidence: 99%